GROWTH AND YIELD RESPONSE OF NEWLY RELEASED CASSAVA GENOTYPES AND HYBRID MAIZE TO INTERCROPPING - Ekwaro, Benson; Wanaku, Boniface; Katuromunda, Sylvester (International Journal of Research -GRANTHAALAYAH, 2019)
Cassava/maize intercrops have been reported to be highly productive, mainly because of their different growth patterns. However, there is limited information on the influence of maize planting density in the cassava/maize intercrop on the performance of hybrid maize and improved cassava genotypes in Uganda. Thus, this study determined whether recently released cassava genotypes which are selected on the basis of monocrop performance, would perform equally well when intercropped with hybrid maize varieties. Cassava genotypes NAROCASS 1 and NASE 14 intercropped with Longe 6H maize were evaluated using randomized complete block design and three replications. Treatments were: Sole maize (SM), sole cassava (SC), alternate rows of cassava and maize (1C:1M), and one row of cassava alternating with two rows of maize (1C:2M). Intercropping significantly increased the maize plant heights in the 1C:2M system than in sole maize. Cob length and number of rows per cob decreased as the plant population density increased. Maize grain yield under the 1C:1M system was comparable to that of sole cropping. The 1C:2M system gave significantly reduced grain yields when compared with those at 1C:1M. Cassava root yield decreased in the order (SM>1C:1M>1C:2M). Although the yields of both cassava and maize under sole cropping were higher than their intercrop counterparts, intercropping was more productive than sole cropping as evidenced by the land equivalent ratios.